Transformation conditions in an Fe-based shape memory alloy: an experimental study - Tanaka, K.; Watanabe, T. (Archives of Mechanics, 1999)
Martensite and austenite start conditions are studied experimentally in an Fe-9%Cr-5%Ni-14%Mn-6%Si polycrystalline SMA under combined tension/compression-torsion loads. The martensite start condition is represented by an oval cone in the stress-temperature space, thus being different from the von Mises theory. The third invariant of the stress deviator has a marked effect. The austenite start condition is expressed by a polygonal cone in the same stress-temperature space. Each side of the cone corresponds to the martensite variants preferably induced during mechanical loading. The direction of the austenite start plane is determined by the direction of loading whereas the amount of variants governs the position of the plane.